2010
DOI: 10.3109/13561820903123102
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the need for homophily in referral criteria: The case of clergy referrals to mental health professionals in Singapore

Abstract: Homophily, the tendency to seek out those who are similar, is a powerful force in structuring the relations that people have in a variety of social settings including the selection of partnerships. Despite this, attitudinal homophily has seldom been discussed in relation to referral practices, an important consideration in health care delivery. In this paper Christian clergy in Singapore are examined as to the extent they impose homophily as a selection criteria for referrals to mental health professionals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Low referral rates by clergy were also predicted by poor past interactions between clergy (or their parishioners) and mental health professionals (e.g., clergy referring a client and never hearing back from the counselor, or getting reports back from referred clients who suggested that the counselor was perceived to be religiously insensitive or unknowledgeable). In addition, referring clergy members tended to look for counselors they knew personally and for those who had traits (e.g., theological beliefs, faith commitments) that the clergy thought would not undermine the faith of the clients (see Mathews, 2010).…”
Section: Systemic Perspective Of R/s Integrationmentioning
confidence: 99%
“…Low referral rates by clergy were also predicted by poor past interactions between clergy (or their parishioners) and mental health professionals (e.g., clergy referring a client and never hearing back from the counselor, or getting reports back from referred clients who suggested that the counselor was perceived to be religiously insensitive or unknowledgeable). In addition, referring clergy members tended to look for counselors they knew personally and for those who had traits (e.g., theological beliefs, faith commitments) that the clergy thought would not undermine the faith of the clients (see Mathews, 2010).…”
Section: Systemic Perspective Of R/s Integrationmentioning
confidence: 99%